Psychometric assessment of the Neonatal Abstinence Scoring System and the MOTHER NAS Scale. Issue 5 (11th June 2016) - Jones, Hendrée E.; Seashore, Carl; Johnson, Elisabeth; Horton, Evette; O'Grady, Kevin E.; Andringa, Kim; Grossman, Matthew R.; Whalen, Bonny; Holmes, Alison Volpe
Abstract : Background and Objectives: The present study examined the psychometric characteristics of the Neonatal Abstinence Scoring System (NASS; "Finnegan Scale") and the MOTHER NAS Scale (MNS). Methods: Secondary analysis of data from 131 neonates from the Maternal Opioid Treatment: Human Experimental Research (MOTHER) study, a randomized trial in opioid‐dependent pregnant women administered buprenorphine or methadone. Results: Both the NASS and MNS demonstrated poor psychometric properties, with internal consistency (Cronbach's αs) failing to exceed .62 at first administration, peak NAS score, and NAS treatment initiation. Conclusions: Findings support the need for development of a NAS measure based on sound psychometric principles. Scientific Significance: This study found that two frequently used measures of neonatal abstinence syndrome suffer inadequacies in regard to their basic measurement characteristics. (Am J Addict 2016;25:370–373)